Characteristics of Young Horticultural Farmers in Malang Regency - Eri Yusnita Arvianti; Masyhuri Masyhuri; Lestari Rahayu Waluyati; Dwidjono Hadi Darwanto (Agro Ekonomi, 2019)
The horticulture subsector occupies a strategic position in the development of Indonesia's agriculture sector. Farmers have an important role in developing agriculture and promoting the agricultural sector in Indonesia. Therefore this paper aims (1) to find out the distribution of characteristics of young farmers in Malang Regency, (2) to know the managerial capacity and empowerment of young farmers in horticultural agriculture in Malang Regency. This research was conducted in five villages in Malang Regency in 2018. These villages were Codo Village, Dampit Village, Punten Village, Gempol Village, and Ngantru Village. The sample is determined by census with a sample size of 195. The analytical method used is descriptive method. Data obtained using interviews through questionnaires. The results showed that the characteristics of young horticultural farmers in Malang Regency were mostly in their 30s and men. The level of education of young horticultural farmers is still low and on average has 9 years of agricultural experience with low land ownership. An intensive policy is needed for young farmers in terms of land ownership. Most farmers have used cellphones or gadgets to carry out agricultural transactions. Most young horticultural farmers in Malang Regency already have good managerial capacity, but in terms of empowerment is still not optimal. The government and farmer groups need to increase their role in supporting the agriculture of young horticultural farmers to be more developed so that young farmers in Malang Regency do not leave their jobs in the agricultural sector..